Friends. Season 6 [videorecording (DVD)] - Aniston, Jennifer; Cox, Courteney, 1964-; Kudrow, Lisa; LeBlanc, Matt; Perry, Matthew, 1969-2023; Schwimmer, David, 1966- (Warner Bros. Entertainment Inc., 2019)
"An apartment blaze sends Rachel and Phoebe off in new directions, Joey lands a role as costar to a robot, and everyone wonders how their lives might have been. "--Container.